Cover Feature: Crystal Structure of PigA: A Prolyl Thioester‐Oxidizing Enzyme in Prodigiosin Biosynthesis (ChemBioChem 2/2019). (22nd January 2019) - Lee, Cheng‐Chung; Ko, Tzu‐Ping; Chen, Chun‐Ting; Chan, Yueh‐Te; Lo, Shin‐Yi; Chang, Jen‐Yu; Chen, Ya‐Wen; Chung, Ting‐Fang; Hsieh, Hsin‐Ju; Hsiao, Chwan‐Deng; Wang, Andrew H.‐J.
Abstract : The cover feature picture shows the biosynthetic pathway of the three‐pyrrole red pigment prodigiosin in Serratia marcescens, the historical culprit of bleeding bread. The tetrameric enzyme PigA oxidizes carrier‐bound proline and turns out the first pyrrole unit of MBC, which then combines with MAP to form the final product. More information can be found in the full paper by C.‐D. Hsiao, A. H.‐J. Wang et al. onpage 193 in Issue 2, 2019 (DOI:10.1002/cbic.201800409 ).